The United States and Israel: The risk of growing apart. If illiberal democracy prevails in Israel, the special relationship may not survive - Mark A. Heller (Stiftung Wissenschaft und Politik (SWP), 2019)
United States Secretary of State Mike Pompeo's assertion that 'the establishment of Israeli civilian settlements in the West Bank is not per se inconsistent with international law' is merely the latest example of how US and Israeli policies have marched almost in lockstep since Donald Trump's inauguration as president. However, the United States and Israel have shared an intense and intimate relationship that long predates the Trump Administration and goes beyond the chemistry of individual leaders. In many respects, in fact, that relationship is unique in American foreign relations and uniquely critical to Israeli security. It is grounded in a shared narrative of biblically inspired frontier societies that have gathered in immigrants and refugees, tamed the wilderness, and built liberal democracy. This explains the broadly receptive environment in the United States for the message of US-Israeli commonality. Nevertheless, the durability of the relationship is not guaranteed. If the societies and political cultures of the two countries either continue to develop along parallel, illiberal lines or shift simultaneously in a more liberal direction, the connection between them will be preserved, or even strengthened. However, if they diverge, and especially if Israel maintains its rightward drift while America moves in an opposite direction, the normative foundation of the relationship will erode, with ominous implications for Israel.
Keywords: 320